Enteric viruses' dissemination in a private reserve of natural heritage. (23rd February 2018) - Fumian, T.M.; Victoria, M.; Vieira, C.B.; Fioretti, J.M.; Rocha, M.S.; Prado, T.; Guimarães, F.R.; da Gama, N.P.; de Oliveira, J.M.; Mendes, A.C.O.; Gaspar, A.M.C.; Santos, J.D.O.; et al.
Abstract: This study aimed to assess anthropogenic impact of surrounding population in the Private Reserve of Natural Heritage at Pantanal, the world's largest freshwater wetland ecosystem located in the centre of South America. Viral aetiological agents of acute gastroenteritis as rotavirus A (RVA), noroviruses, human adenoviruses, klassevirus and of hepatitis, as hepatitis A virus, were investigated in different aquatic matrices. Annual collection campaigns were carried out from 2009 to 2012, alternating dry and rainy seasons. Viral particles present in the samples were concentrated by the adsorption–elution method, with negatively charged membranes, and detected by qualitative and quantitative PCR. From a total of 43 samples at least one virus was detected in 65% (28) of them. Viruses were detected in all matrices with concentrations ranging from 2 × 10 2 to 8·3 × 10 4 genome copies per litre. A significant higher RVA frequency was observed in the dry season. Our data revealing dissemination of human enteric viruses in water matrices both inside and outside the reserve could be useful to trace faecal contamination in the environment and to minimize the risk of infection by exposure of susceptible individuals. Significance and Impact of the Study: This study is part of a collaborative project designed to investigate the environmental and health conditions of the Private Reserve of Natural Heritage at Pantanal, the largest seasonally flooded wetland in the world. The project aimed to promote health and quality of human and wildlife extending technical‐scientific knowledge about pathogens present in the region. By assessing the occurrence of human enteric viruses in different water matrices we demonstrated the anthropogenic impact of surrounding population and pointed out the potential risk of infection by exposure of susceptible individuals. Abstract : Significance and Impact of the Study: This study is part of a collaborative project designed to investigate the environmental and health conditions of the Private Reserve of Natural Heritage at Pantanal, the largest seasonally flooded wetland in the world. The project aimed to promote health and quality of human and wildlife extending technical‐scientific knowledge about pathogens present in the region. By assessing the occurrence of human enteric viruses in different water matrices we demonstrated the anthropogenic impact of surrounding population and pointed out the potential risk of infection by exposure of susceptible individuals.